The careerist : over 100 ways to get ahead at work - Rigby, Rhymer (London, United Kingdom : Kogan Page Limited, 2012)
The Careerist - 100 ways to get ahead at work is a handy, quick-fix reference guide on how to improve your career prospects. Based on the weekly column in the Financial Times by Rhymer Rigby, it provides expert advice for those difficult career moments such as how to: do presentations, work a room, delegate effectively, market yourself, bounce back from failure, sack someone, use extracurricular activities, be more ambitious, change sector, make a good impression, ask for a pay rise, future proof your career, get headhunted, socialize with colleagues, find a mentor, deal with fights at work.
1. Moving onwards and upwards -- 2. Work and the rest of your life -- 3. Working nicely with others -- 4. Networks, Power and Influence -- 5. Keeping up appearances -- 6. Business or pleasure? -- 7. Being the bigger, better manager -- 8. Goals, and career planning, business education and other longer-term stuff -- 9. Practical ways to get ahead -- 10. Slightly more abstract ways to get ahead -- 11. The stuff nobody likes at work.
Includes bibliographical references.
Keywords: BUSINESS & ECONOMICS -- CAREERS INTERNSHIPS